Optimizing the Digitalization of Storage and Sales of Urban Farming Products as an Effort for Food Security and Improving the Local Economy - Wirati, Triantya Wahyu; Assyifa, Allya Sofiana; Afif, Mochamad Fakhriy (Journal of Digital Business and Innovation Management, 2024)
Urbanization is moving the human population from rural to urban areas. In rural areas, more land can be used for farming, while in urban areas, there is not much land for farming. Urban farming is a solution for people moving from rural to urban areas. Urban farming is the cultivation of plants in big cities with limited land. Hydroponics is a method of cultivating plants without using soil but rather using water flow for nutrient distribution; this method has the advantage of more efficient use of water and faster growth to produce quality fruit. Quality fruit is very influential in storage because it can last longer than fruit with poor conditions. The aim of this research is to analyze the design of an e-commerce website system for urban farming to optimize the potential of urban farming through the appropriate and strategic application of information technology. It is hoped that this research will support the growth and sustainability of urban agriculture but also open up new opportunities in marketing, inventory management, and efficient operational management.